Nanocrystalline barium titanate dielectric ceramic, preparation method thereof and ceramic capacitor
The chemical coating and controlled sintering process for nanocrystalline barium titanate dielectric ceramics address the challenges of MLCCs by achieving smaller grain sizes and higher dielectric constants, resulting in capacitors with improved capacitance and reliability.
Patent Information
- Application Number
- CN202411356706.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
AI Technical Summary
Existing multilayer ceramic capacitors (MLCCs) face challenges in achieving miniaturization with large capacity and high reliability due to limitations in particle size and dielectric properties of barium titanate dielectric ceramics.
A chemical coating method and two-stage sintering process are employed to prepare nanocrystalline barium titanate dielectric ceramics with a core-shell structure, using dopants like Ho, Y, Dy, Ca, Mg, Mn, and Zn to control grain size and enhance dielectric properties, followed by a controlled sintering process to achieve smaller grain sizes and higher dielectric constants.
The method results in nanocrystalline barium titanate dielectric ceramics with grain sizes between 100-150 nm, a relative dielectric constant of 1863-2584, and dielectric loss of 0.01-0.02, suitable for producing small-sized ceramic capacitors with excellent capacitance performance.
Smart Images

Figure CN119143500A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a nanocrystalline barium titanate dielectric ceramic and a preparation method thereof, and a ceramic capacitor. Background Art
[0002] With the advancement of world science and technology and the rapid development of the electronics industry, high-performance capacitors, core electronic components, are also being updated at a very high speed, and have extensive and important applications in different fields such as mobile phones, computers, automobiles, the Internet of Things, base stations, automobiles, and the military. As one of the high-performance capacitor components, multilayer ceramic capacitors (MLCC) have many advantages such as small size, large capacitance, ability to control the amount of current flowing through the circuit, noise elimination and loss reduction, and high stability. They are widely used in terminal applications and electronic control equipment. As MLCC gradually develops towards miniaturization, large capacity, and high reliability, higher requirements are put forward for the particle size and dielectric properties of barium titanate dielectric ceramics. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a nanocrystalline barium titanate dielectric ceramic and a preparation method thereof and a ceramic capacitor, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.
[0004] As a first aspect of the present invention, a method for preparing nanocrystalline barium titanate dielectric ceramics is provided, comprising: Adding barium titanate into the first solvent and subjecting it to ultrasonic atomization to obtain barium titanate slurry; Adding holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate, and zinc acetate to an inorganic solvent to obtain an inorganic doping solution, and adding tetraethoxysilane to a second solvent to obtain an organic doping solution; The barium titanate slurry, the inorganic doping solution and the organic doping solution are uniformly mixed to obtain a mixed slurry; The pH of the mixed slurry is adjusted to alkaline and allowed to settle, and then dried, screened and pre-calcined for the first time to obtain a powder; After the powder is screened for the second time, it is evenly mixed with the binder, screened for the third time, granulated, and pressed into a green embryo; After debinding and sintering, the green embryo can obtain nanocrystalline barium titanate dielectric ceramics.
[0005] As a second aspect of the present invention, a nanocrystalline barium titanate dielectric ceramic is provided, which is prepared by the above-mentioned preparation method, wherein the nanocrystalline barium titanate dielectric ceramic has a core-shell structure in which barium titanate is wrapped by holmium oxide, yttrium oxide, dysprosium oxide, calcium oxide, magnesium oxide, manganese oxide, zinc oxide and silicon oxide.
[0006] As a third aspect of the present invention, a ceramic capacitor is provided, which is made of the above-mentioned nanocrystalline barium titanate dielectric ceramic.
[0007] In an embodiment of the present invention, barium titanate and dopants of holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate, zinc acetate and tetraethoxysilicon are used as raw materials, and a chemical coating method and a sintering process are adopted to prepare nanocrystalline barium titanate dielectric ceramics. Through the chemical coating method, a uniform coating layer of doped ions can be effectively formed on the surface of barium titanate, thereby controlling the formation of a core-shell structure and improving the performance of nanocrystalline barium titanate dielectric ceramics. At the same time, the sintering process is adopted, which not only ensures the density of the nanocrystalline barium titanate dielectric ceramics, but also effectively controls the growth process of the grains, which is conducive to obtaining nanocrystalline barium titanate dielectric ceramics with smaller grain size. The grain size of the obtained nanocrystalline barium titanate dielectric ceramics is between 100-150nm, the relative dielectric constant is 1863-2584, and the dielectric loss is 0.01-0.02. In addition, the preparation method of the nanocrystalline barium titanate dielectric ceramics provided by the present invention is simple to operate, the process is controllable, suitable for large-scale promotion, and has broad application prospects. The ceramic capacitor made by using the nanocrystalline barium titanate dielectric ceramic provided by the present invention has the characteristics of small size and excellent capacitance performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a schematic diagram of the structure of a high-capacitance multilayer ceramic capacitor (MLCC);
[0009] Figure 2 This is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in the comparative example of Example 1 of the present invention;
[0010] Figure 3 This is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in Example 2 of the present invention;
[0011] Figure 4 This is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure.
[0013] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.
[0014] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).
[0015] Figure 1 This is a schematic diagram of the structure of a high-capacitance multilayer ceramic capacitor. Figure 1 As shown in the figure, the internal structure of a high-capacitance multilayer ceramic capacitor (MLCC) is a multilayer alternating and parallel stacking of dielectric ceramic bodies and internal electrode materials, which are then coated with end electrodes and co-fired into a component.
[0016] The calculation method of the total capacitance C of MLCC is shown in formula (1): Formula (1); Among them, ε r is the relative dielectric constant, ε 0 is the vacuum dielectric constant, s is the overlap area of the internal printed electrodes, n is the number of internal dielectric layers, and d is the thickness of the dielectric layer.
[0017] From formula (1), it can be seen that one of the important means to achieve large capacity and design a specific small size MLCC is to make each dielectric layer thinner and stack more dielectric layers. The grain size of the ceramic powder is the most important factor affecting the thickness of the dielectric layer. The preparation of dielectric materials with smaller particle size and larger capacitance within a limited volume is a key requirement for the research and development of dielectric ceramics.
[0018] Based on this, the present invention provides a nanocrystalline barium titanate dielectric ceramic and a preparation method thereof and a ceramic capacitor, which adopts a chemical precipitation coating method and a sintering process, especially a two-stage sintering process, through Ho 3+ , Y 3+ 、Dy3+ , Ca 2+ Mg 2+ , Mn 2+ 、Zn 2+ and Si(OC 2 H 5 ) 4 By doping modification, nanocrystalline barium titanate dielectric ceramics are prepared, which maintains a high dielectric constant while reducing the grain size, further improving the dielectric properties of nanocrystalline barium titanate dielectric ceramics, thereby better meeting actual application needs.
[0019] Specifically, as a first aspect of the present invention, a method for preparing nanocrystalline barium titanate dielectric ceramics is provided, comprising: Adding barium titanate into the first solvent and subjecting it to ultrasonic atomization to obtain barium titanate slurry; adding holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate and zinc acetate into an inorganic solvent to obtain an inorganic doping solution, and adding tetraethoxysilane into a second solvent to obtain an organic doping solution; The barium titanate slurry, the inorganic doping solution and the organic doping solution are uniformly mixed to obtain a mixed slurry; The pH of the mixed slurry is adjusted to alkaline and allowed to settle, and then dried, screened and pre-calcined for the first time to obtain a powder; After the powder is screened for the second time, it is evenly mixed with the binder, screened for the third time, granulated, and pressed into a green embryo; After debinding and sintering, the green embryo can obtain nanocrystalline barium titanate dielectric ceramics.
[0020] In an embodiment of the present invention, barium titanate and dopants such as holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate, zinc acetate, and tetraethoxysilicon are used as raw materials, and a chemical coating method and a sintering process are adopted to prepare nanocrystalline barium titanate dielectric ceramics. Through the chemical coating method, a uniform coating layer of doped ions can be effectively formed on the surface of the barium titanate, thereby controlling the formation of a core-shell structure and improving the performance of the nanocrystalline barium titanate dielectric ceramics. At the same time, the sintering process is adopted, which not only ensures the density of the nanocrystalline barium titanate dielectric ceramics, but also effectively controls the growth process of the grains, which is conducive to obtaining nanocrystalline barium titanate dielectric ceramics with smaller grain size. The preparation method of the nanocrystalline barium titanate dielectric ceramics provided by the present invention is simple to operate, has a controllable process, is suitable for large-scale promotion, and has broad application prospects.
[0021] According to an embodiment of the present invention, in terms of molar percentage, the content of barium titanate is 92.4-93.7 mol%, the content of holmium nitrate is 1 mol%, the content of yttrium nitrate is 0.3 mol%, the content of dysprosium nitrate is 2 mol%, the content of calcium nitrate is 0.8-1.5 mol%, the content of magnesium nitrate is 0.4-0.8 mol%, the content of manganese acetate is 0.3 mol%, the content of zinc acetate is 0.8-1.0 mol%, and the content of tetraethoxysilane is 0.7 mol%. Among them, Ho 3+ , Y 3+ and Dy 3+ The doping of Ca can improve the dielectric constant and temperature stability of nanocrystalline barium titanate dielectric ceramics; 2+ and Mg 2+ The doping of Mn can adjust the grain size of nanocrystalline barium titanate dielectric ceramics; 2+ The doping of Zn can make the nanocrystalline barium titanate dielectric ceramics have certain anti-reduction and anti-aging properties; 2+ and Si(OC 2 H 5 ) 4 The doping can promote sintering, reduce the sintering temperature of nanocrystalline barium titanate dielectric ceramics, and inhibit the grain size growth of dielectric ceramics. The present invention uses a chemical coating method to form a doped ion coating layer on the surface of barium titanate, and the dopant anions used are decomposed into gas and escaped during sintering, thereby avoiding the influence on the electrode when preparing ceramic capacitors.
[0022] According to an embodiment of the present invention, the green embryo after debinding is sintered. The temperature control and time arrangement during the sintering process also affect the growth and distribution of grains, and further affect the key parameters such as the dielectric constant and piezoelectric properties of the barium titanate dielectric ceramic. In this regard, the present invention provides a two-stage sintering process, and the specific sintering process includes: first heating to 1200-1240°C in a reducing atmosphere, then cooling to 1000°C, and keeping warm for 4 hours. The reducing atmosphere is N 2 With H 2A mixed gas with a flow ratio of 49-47:1-3. When preparing ceramic capacitors, the nanocrystalline barium titanate dielectric ceramics provided by the present invention are obtained by stacking the debinding green embryo and the electrode material in multiple layers and coating the end electrodes before sintering. Therefore, it is necessary to sinter in a reducing atmosphere to avoid electrode oxidation affecting subsequent use. During sintering, the temperature is first raised to 1200-1240°C to make the nanocrystalline barium titanate dielectric ceramics denser, and then cooled to 1000°C to allow the grains to grow slowly and the grain size to be more controllable. In the first stage of the sintering process, high-temperature heating is used to effectively eliminate the pores in the debinding green embryo at a higher temperature, significantly improving the density of the nanocrystalline barium titanate dielectric ceramics, thereby enhancing the mechanical and electrical properties of the nanocrystalline barium titanate dielectric ceramics. In the second stage of the sintering process, the temperature is lowered and kept warm for a long time to promote the bonding and diffusion between the barium titanate particles, forming a uniform and dense microstructure, while also avoiding excessive grain size growth at high temperatures. Ultimately, a dielectric ceramic material with a dense structure and a grain size controlled at a smaller size is obtained.
[0023] According to an embodiment of the present invention, the first solvent includes any one of isopropanol, ethanol, and water, and barium titanate is added to the first solvent and dispersed evenly so as to be evenly mixed with subsequent dopants. The inorganic solvent includes water, and holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate, and zinc acetate are added to the inorganic solvent to facilitate uniform mixing with barium titanate and other dopants. The second solvent includes a mixed solvent having a volume ratio of ethanol to water of 2.5-3.5:1, and tetraethoxysilane is soluble in ethanol and slightly soluble in water, so tetraethoxysilane is added to a mixed solvent of ethanol and water to facilitate uniform mixing with barium titanate and other dopants. The volume ratio of the first solvent, the inorganic solvent, and the second solvent is 20-40:1-4:1 to control the ratio of barium titanate slurry, inorganic doping solution, and organic doping solution, and improve the grain size and dielectric properties of nanocrystalline barium titanate dielectric ceramics.
[0024] According to an embodiment of the present invention, the main purpose of drying is to remove the solvent used in the chemical coating process. The drying temperature will affect the morphology and size of barium titanate. At high temperatures, barium titanate will agglomerate or sinter, resulting in an increase in the size of barium titanate, which will affect the microstructure and properties of nanocrystalline barium titanate dielectric ceramics. Therefore, the drying temperature is preferably 80-120°C. The main purpose of pre-sintering is to sinter the hydroxide of the doped element into an oxide. The pre-sintering temperature and time are key factors affecting the pre-sintering effect. Appropriate pre-sintering temperature and time can control the generation of oxides without affecting other properties of the powder. Therefore, the pre-sintering temperature is preferably 450°C, and the pre-sintering time is preferably 2h. Debinding is to gasify and burn the binder (i.e., paraffin) in the green embryo by heating to avoid the formation of pores in the nanocrystalline barium titanate dielectric ceramics due to the volatilization of organic matter during the subsequent sintering process, thereby reducing its density and even causing cracking. The debinding temperature and time have a significant effect on the debinding effect. The debinding temperature needs to be set within an appropriate range to ensure that the binder can be fully gasified and burned off while avoiding unnecessary thermal damage to the green embryo. Too low a debinding temperature may lead to incomplete debinding, while too high a temperature may cause pyrolysis or phase change of the green embryo. The debinding time also needs to be controlled, and sufficient time can ensure that the debinding process is fully carried out. Therefore, the debinding temperature is preferably 550℃, and the debinding time is preferably 2h.
[0025] According to an embodiment of the present invention, adjusting the pH of the mixed slurry to alkaline and allowing it to settle comprises: adjusting the pH of the mixed slurry to 10.0-10.5 by 3-4 times the volume of diluted ammonia water, stirring for 1 hour, and allowing it to settle for 12-24 hours. By adjusting the pH value, the doping element can be precipitated on the surface of barium titanate in the form of hydroxide to form a dense coating. By adjusting the pH by ammonia water, the ammonia water is gasified and removed during the subsequent pre-firing process without affecting the performance of the nanocrystalline barium titanate dielectric ceramic. Allowing it to settle to age the mixed slurry further solidifies the coating on the surface of the barium titanate to form a more stable and dense coating, which helps to improve the mechanical strength and weather resistance of the nanocrystalline barium titanate dielectric ceramic.
[0026] According to an embodiment of the present invention, the ultrasonic atomization time is 3-5h, and the barium titanate is uniformly dispersed in the first solvent by ultrasonic atomization. Screening with a mesh size of 40 or more is used to avoid the agglomeration of barium titanate from affecting the subsequent pre-sintering, debinding and sintering processes. Specifically, the first screening and the second screening are screened with a 40-mesh screen, and the third screening is screened with an 80-mesh screen. The binder is paraffin powder, and its added mass is 7% of the mass of the powder. The barium titanate is bonded to the oxide of the doping element by the binder to make it easy to form.
[0027] As a second aspect of the present invention, a nanocrystalline barium titanate dielectric ceramic is provided, which is prepared by the above-mentioned preparation method, wherein the nanocrystalline barium titanate dielectric ceramic has a core-shell structure of barium titanate wrapped by holmium oxide, yttrium oxide, dysprosium oxide, calcium oxide, magnesium oxide, manganese oxide, zinc oxide and silicon oxide.
[0028] In an embodiment of the present invention, doped ions are coated on the surface of barium titanate by a chemical coating method, and finally a core-shell structure of barium titanate coated with holmium oxide, yttrium oxide, dysprosium oxide, calcium oxide, magnesium oxide, manganese oxide, zinc oxide, and silicon oxide is formed. The grain size and dielectric properties of the nanocrystalline barium titanate dielectric ceramic are controlled by doping modification and a two-stage sintering process.
[0029] According to an embodiment of the present invention, the average size of the nanocrystalline barium titanate dielectric ceramic is 100-150 nm, the relative dielectric constant is 1863-2584, and the dielectric loss is 0.01-0.02.
[0030] As a third aspect of the present invention, a ceramic capacitor is provided, which is made of the above-mentioned nanocrystalline barium titanate dielectric ceramic. The ceramic capacitor made of the nanocrystalline barium titanate dielectric ceramic provided by the present invention has the characteristics of small size and excellent capacitance performance.
[0031] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.
[0032] Example 1
[0033] This embodiment 1 provides a nanocrystalline barium titanate dielectric ceramic, and the preparation method thereof is described as follows.
[0034] BaTiO 3 and dopant Ho(NO 3 ) 3 •6H 2 O、Y(NO 3 ) 3 •6H 2 O、Dy(NO 3 ) 3 •6H 2 O, Ca(NO 3 ) 2 •4H 2 O、Mg(NO 3 )2 •6H 2 O、Mn(CH 3 COO 2 •4H 2 O、Zn(CH 3 COO 2 、Si(OC 2 H 5 ) 4 The ingredients are prepared according to the molar percentage of the doping elements in each dopant as shown in Table 1.
[0035] Table 1 Doping element content in nanocrystalline barium titanate dielectric ceramic dopant of Example 1
[0036] About 9 g of BaTiO 3 The raw material powder was placed in a 500 mL beaker, 200 mL of isopropanol was added, and ultrasonic atomization dispersion was performed for 4 hours to obtain a stable barium titanate slurry.
[0037] Will Ho(NO 3 ) 3 •6H 2 O、Y(NO 3 ) 3 •6H 2 O、Dy(NO 3 ) 3 •6H 2 O, Ca(NO 3 ) 2 •4H 2 O、Mg(NO 3 ) 2 •6H 2 O、Mn(CH 3 COO 2 •4H 2 O、Zn(CH 3 COO 2 Dissolve in 20 mL of deionized water to obtain an inorganic doping solution; Si(OC 2 H 5 ) 4 The organic doping solution was obtained by dissolving it in a mixed solvent of 10 mL of ethanol and deionized water in a volume ratio of 3:1.
[0038] The inorganic doping solution and the organic doping solution are respectively added into the barium titanate slurry dispersed by ultrasonic atomization and mixed evenly to obtain a mixed slurry.
[0039] Add 3 times the volume of diluted ammonia water dropwise to the mixed slurry while stirring continuously, adjust the pH of the barium titanate slurry to 10, continue stirring for 1 hour, let it stand and settle for 12 hours, place it in an infrared oven, dry it at 100°C and pass it through a 40-mesh sieve 3 times, and pre-calcine it at 450°C for 2 hours to obtain powder.
[0040] After the powder is passed through a 40-mesh sieve three times, paraffin powder is added as a binder, the mass of which is 7% of the mass of the powder, and mixed evenly. After passing through an 80-mesh sieve three times, a powder tablet press is used to press the powder into a green body at a pressure of 2 MPa.
[0041] The green body was kept at 550 °C for 2 h for debinding, and the debinded green body was placed in an atmosphere furnace for sintering. The atmosphere was controlled to be N with a flow ratio of 47:3. 2 and H 2 The mixed gas is first heated to 1240°C without heat preservation, then cooled to 1000°C and kept at this temperature for 4 hours for sintering to obtain nanocrystalline barium titanate dielectric ceramics.
[0042] Example 2
[0043] This embodiment 2 provides a nanocrystalline barium titanate dielectric ceramic, which differs from the preparation method of the nanocrystalline barium titanate dielectric ceramic in embodiment 1 in that the ingredients are prepared according to the molar percentage of the doping elements in each dopant as shown in Table 2.
[0044] Table 2 Doping element content in nanocrystalline barium titanate dielectric ceramic dopant of Example 2
[0045] Comparative Example 1
[0046] This comparative example 1 provides a nanocrystalline barium titanate dielectric ceramic, and the difference between the preparation method of the nanocrystalline barium titanate dielectric ceramic in the comparative example 1 and the preparation method of the nanocrystalline barium titanate dielectric ceramic in the comparative example 1 is that the temperature is directly raised to 1180° C. and kept at this temperature for 4 hours during sintering.
[0047] Testing and Characterization
[0048] The nanocrystalline barium titanate dielectric ceramics obtained in the above-mentioned embodiments and comparative examples were subjected to relevant tests and characterizations.
[0049] The nanocrystalline barium titanate dielectric ceramics obtained in Examples 1-2 and Comparative Example 1 were tested using a scanning electron microscope (SEM).
[0050] Figure 2 is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in Example 1 of the present invention, Figure 3 is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in Example 2 of the present invention, Figure 4This is a scanning electron microscope image of the nanocrystalline barium titanate dielectric ceramic in Comparative Example 1 of the present invention.
[0051] Furthermore, the dielectric properties of the nanocrystalline barium titanate dielectric ceramics obtained in Examples 1-2 and Comparative Example 1 were tested, and the test results are shown in Table 3.
[0052] Table 3 Test results of grain size and dielectric properties of nanocrystalline barium titanate dielectric ceramics in Examples 1-2 and Comparative Example 1
[0053] from Figure 2-Figure 4 As can be seen from Table 3: When Ca 2+ With Mg 2+ When the doping content increases from 0.8mol% and 0.4mol% to 1.5mol% and 0.8mol%, the grain size of nanocrystalline barium titanate dielectric ceramics is further reduced, but the pores between the grains increase, the density of nanocrystalline barium titanate dielectric ceramics decreases after sintering, and the dielectric constant decreases. This is mainly due to the fact that under the action of high temperature, Ca 2+ With Mg 2+ A low melting point compound is formed at the grain boundary, which is equivalent to hindering the movement of the grain boundary, thereby inhibiting the growth of the grains; at the same time, due to the obstruction of the movement of the grain boundary, the pores between the grains are not completely eliminated, resulting in a decrease in the density of the nanocrystalline barium titanate dielectric ceramic. By comparing Comparative Example 1 with Example 1, it can be seen that the two-stage sintering process can significantly reduce the grain size of the dielectric ceramic while maintaining the dielectric constant and dielectric loss without obvious degradation, proving that the sintering scheme is feasible.
[0054] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing nanocrystalline barium titanate dielectric ceramics, include: Adding barium titanate into the first solvent and subjecting it to ultrasonic atomization to obtain barium titanate slurry; Adding holmium nitrate, yttrium nitrate, dysprosium nitrate, calcium nitrate, magnesium nitrate, manganese acetate, and zinc acetate to an inorganic solvent to obtain an inorganic doping solution, and adding tetraethoxysilane to a second solvent to obtain an organic doping solution; The barium titanate slurry, the inorganic doping solution and the organic doping solution are uniformly mixed to obtain a mixed slurry; The pH of the mixed slurry is adjusted to alkaline and allowed to settle, and then dried, screened and pre-calcined for the first time to obtain a powder; After the powder is screened for the second time, it is evenly mixed with a binder, screened for the third time, granulated, and pressed to obtain a green embryo; After the green body is debinded and sintered, nanocrystalline barium titanate dielectric ceramics are obtained.
2. The preparation method according to claim 1, in, In terms of mole percentage, the content of barium titanate is 92.4-93.7 mol%, the content of holmium nitrate is 1 mol%, the content of yttrium nitrate is 0.3 mol%, the content of dysprosium nitrate is 2 mol%, the content of calcium nitrate is 0.8-1.5 mol%, the content of magnesium nitrate is 0.4-0.8 mol%, the content of manganese acetate is 0.3 mol%, the content of zinc acetate is 0.8-1.0 mol%, and the content of tetraethoxysilicon is 0.7 mol%.
3. The preparation method according to claim 1, in, The sintering comprises: performing two-stage sintering in a reducing atmosphere; Wherein, the reducing atmosphere is N 2 With H 2 Mixed gas with a flow ratio of 49-47:1-3; The two-stage sintering includes: heating to 1200-1240° C., cooling to 1000° C., and keeping the temperature for 4 hours.
4. The preparation method according to claim 1, in, The first solvent includes any one of isopropanol, ethanol, and water, the inorganic solvent includes water, and the second solvent includes a mixed solvent of ethanol and water in a volume ratio of 2.5-3.5:1; The volume ratio of the first solvent, the inorganic solvent and the second solvent is 20-40:1-4:
1.
5. The preparation method according to claim 1, in, The drying temperature is 80-120°C; and / or The pre-firing temperature is 450° C. and the pre-firing time is 2 hours; and / or The debinding temperature is 550° C., and the debinding time is 2 hours.
6. The preparation method according to claim 1, in, The step of adjusting the pH of the mixed slurry to alkaline and allowing the mixed slurry to settle comprises: The pH of the mixed slurry was adjusted to 10.0-10.5 by using 3-4 times the volume of diluted ammonia water, and then stirred for 1 hour, and allowed to settle for 12-24 hours.
7. The preparation method according to claim 1, in, The ultrasonic atomization time is 3-5h; and / or The first screening and the second screening are through a 40-mesh sieve, and the third screening is through an 80-mesh sieve; and / or The binder is paraffin powder, and the mass of the paraffin powder is 7% of the mass of the powder.
8. A nanocrystalline barium titanate dielectric ceramic, prepared by the preparation method according to any one of claims 1 to 7, in, The nanocrystalline barium titanate dielectric ceramic has a core-shell structure in which barium titanate is wrapped by holmium oxide, yttrium oxide, dysprosium oxide, calcium oxide, magnesium oxide, manganese oxide, zinc oxide and silicon oxide.
9. The nanocrystalline barium titanate dielectric ceramic according to claim 8, in, The average size of the nanocrystalline barium titanate dielectric ceramic is 100-150 nm, the relative dielectric constant is 1863-2584, and the dielectric loss is 0.01-0.
02.
10. A ceramic capacitor made of the nanocrystalline barium titanate dielectric ceramic according to any one of claims 8 to 9.
Citation Information
Patent Citations
Chemical coating prepared base metal internal electrode multi-layer ceramic chip capacitor dielectric material
CN101183610A
barium titanate-based X8R ceramic material and preparation method and ceramic capacitor thereof
CN106966719A
Nanocrystalline barium titanate ceramic and preparation method thereof
CN111533553A
High-capacitance-temperature-coefficient barium titanate dielectric material for extremely-high-voltage-resistant MLCC, preparation method and application
CN117088685A
Cited By
Dielectric material for wafer type ceramic capacitor and preparation method and application of dielectric material
CN120058356A
Nanocrystalline anti-reduction temperature stable type barium titanate dielectric ceramic, preparation method thereof and ceramic capacitor
CN121107842A
